Demographic and motivational factors affecting the whole-body donation programme in Nanjing, China: a cross-sectional survey. Issue 9 (6th September 2020) - Jiang, Jiayi; Zhang, Mingyi; Meng, Haojie; Cui, Xiang; Yang, Yuxin; Yuan, Li; Su, Chuan; Wang, Jinfan; Zhang, Luqing
Abstract : Objectives: To investigate the demographics and motivations of whole-body donors in China, and help suggest a solution to the problem of low body donation numbers. Design: A cross-sectional study on body donors in China. Demographic analysis of the donating information of deceased donors and in-depth interviews of potential body donors. Setting: Eleven districts in Nanjing, China. Participants: Deceased whole-body donors who had donated their bodies to the body donation receiving station of Nanjing Medical University between 1 July 2009 and 30 June 2019 (n=835), and living registered whole-body donors (n=68). Results: Among the whole-body donor population, the numbers of males, people older than 65 years and those working as teachers, government officials, medical staff and farmers were significantly higher than those of the general Nanjing population. Donors with an education level of college or above accounted for nearly half of the deceased donors, and considered donating their bodies earlier in their lives than others. Cancer and heart disease were the major causes of death among donors. Interviews of the 68 living donors revealed the following major motivations for the decision to donate: to support medical education; to reduce their children's funeral burden; no longer holding traditional Chinese views on life and death; influence by role models and annoyance at complex funeral ceremonies. Conclusions: Older people, people with an education level of college or above, labourers, teachers, government officials and farmers are the major groups that donate their bodies. Although people's motivations for donation are complex, their desire to support medical education is the most prevalent motivation. By helping focus on target groups for promotional messaging and identifying their prime motivations, this study's findings can provide a reference for promoting body donation in China.